Prognostic and Immunological Role of FUN14 Domain Containing 1 in Pan-Cancer: Friend or Foe? - Yuan, Qingchen; Sun, Na; Zheng, Jiayu; Wang, Yingxuan; Yan, Xiaole; Mai, Wuqian; Liao, Yuhua; Chen, Xiao (Frontiers in Oncology, 2020)
Background FUN14 domain containing 1 (FUNDC1) plays a pivotal role in mitochondrial autophagy (mitophagy), which is closely associated with human immunity. However, the role of FUNDC1 is still underexploited in cancers. This study aims to depict a prognostic landscape of FUNDC1 in pan-cancer and investigate the relationship between FUNDC1 expression and immune infiltration. Methods In this study, we explored expression pattern and prognostic value of FUNDC1 in pan-cancer across multiple databases including ONCOMINE, PrognoScan, GEPIA, and Kaplan-Meier Plotter. Then, by using GEPIA and TIMER databases, we investigated correlations between FUNDC1 expression and immune infiltration in cancers, especially liver hepatocellular carcinoma (LIHC) and lung squamous cell carcinoma (LUSC). Results In general, compared with normal tissue, tumor tissue had higher expression level of FUNDC1. While FUNDC1 showed protective effect on pan-cancer, however, high expression level of FUNDC1 was detrimental to the survival of LIHC patients. Different from cancers like LUSC, LIHC owned significant positive correlations between FUNDC1 expression and immune infiltrates including B cells, CD8+ T cells, CD4+ T cells, neutrophils, macrophages, and dendritic cells. Furthermore, markers of infiltrating immune cells, like tumor-associated-macrophage (TAM), reflected different FUNDC1-related immune infiltration patterns. Conclusion Mitophagy regulator FUNDC1 can serve as a prognostic biomarker in pan-cancer, and affect prognosis via interaction with immune infiltrates.